2015
DOI: 10.1039/c5ra10887j
|View full text |Cite
|
Sign up to set email alerts
|

Novel halogen-free flame retardants based on adamantane for polycarbonate

Abstract: The surface of PC/FR compositions presents a continuous and protective carbon layer with several bubbles and folds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…1,3,5,7-Tetrahydroxyadamantane (AD-(OH) 4 ) was prepared according to the reported literature [23]. DL-LA, GA, pentaerythritol (PT), stannous octoate (Sn(Oct) 2 ), pyrene, N,N-dimethylformamide (DMF, 99.9%, extra dry, water ≤ 30 ppm), 3,3 -dithiodipropionic acid, and triethylamine were purchased from Energy Chemical (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…1,3,5,7-Tetrahydroxyadamantane (AD-(OH) 4 ) was prepared according to the reported literature [23]. DL-LA, GA, pentaerythritol (PT), stannous octoate (Sn(Oct) 2 ), pyrene, N,N-dimethylformamide (DMF, 99.9%, extra dry, water ≤ 30 ppm), 3,3 -dithiodipropionic acid, and triethylamine were purchased from Energy Chemical (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…3), and exhibit decomposition temperatures over 600 C. Clearly, the introduction of the rigid adamantane unit has enhanced the thermal stability of our target polymers. 19,22 Moreover, the higher the adamantane content, the better the thermal stability. For example, the molar ratio of adamantane between MOP-Ad-1 and MOP-Ad-3 is 22.45% and 14.80%, and we found that MOP-Ad-1 was more stable (up to 520 C) than MOP-Ad-3 (up to 480 C).…”
Section: Characterization Of Mop-ad Networkmentioning
confidence: 99%
“…Adamantane and its derivatives, a class of unique compounds with a relatively rigid three-dimensional framework and high physicochemical stability, 19,20 have been employed as suitable building blocks in the preparation of thermostable microporous polymers. 21,22 For instance, Han and co-workers 15 reported networks of hexakis(4-bromophenyl)benzene and diethynylbenzene (HPOP-2), synthesized via Sonogashira coupling, possessed a high Brunauer-Emmett-Teller (BET) surface area of 742 m 2 g À1 but degraded around 280 C. In contrast, Chang et al 18 designed and synthesized novel MOP materials in the same way and all reagents except that 1,3,5,7-tetrakis(4-iodophenyl)adamantane were used in place of hexakis(4-bromophenyl)benzene, showing a high BET surface area (up to 665 m 2 g À1 ) and a degradation temperature around 340 C. They attributed the enhanced thermal stability to the introduction of adamantane into the molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of biological activities of adamantane derivatives have also been reported [5][6][7]. They find use in polymer synthesis [8], the design of nanostructured materials [9,10], ionic liquids [11], and coordination chemistry [12,13]. In addition, arrangement of azoles around a rigid linker makes azolyladamantanes perfect auxiliary ligands for metal-organic framework design; however, only a few examples of such ligands (with 4H-1,2,4-triazolyl and tetrazolyl moieties) have been reported [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%